1983
DOI: 10.1007/bf00393645
|View full text |Cite
|
Sign up to set email alerts
|

Molecular size limit for movement in the symplast of the Elodea leaf

Abstract: A range of water-soluble fluorescent dyes and dye conjugates have been injected into cells in Elodea canadensis Michx. leaves. All compounds are unable to cross the plasmalemma between living cells and the external solution, are not degraded to other fluorescent compounds by tissue homogenates, and do not affect cytoplasmic streaming. Despite being unable to cross the plasmalemma, molecules up to 874 dalton pass from cell to cell, smaller molecules showing greater mobility. The conjugate of fluorescein isothio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(71 citation statements)
references
References 16 publications
2
68
1
Order By: Relevance
“…From electron microscopy studies, the cytoplasmic sleeve of a PD in mesophyll cells appears to be subdivided into microchannels 1.5 to 2.5 nm in diameter (Ding et al, 1992). Microinjection experiments reveal that the basal SEL of mesophyll PD is 1 kD; this SEL corresponds to a 0.75-nm Stokes radius (Tucker, 1982;Goodwin, 1983;Wolf et al, 1989) and predicts a basal diameter for a microchannel of 1.5 nm, consistent with the dimensions observed by using electron microscopy. Microinjection studies also show that PD in different cell types can have different basal SELs.…”
Section: Symplastic Transport Via Dynamic Plasmodesmal Channelssupporting
confidence: 59%
See 1 more Smart Citation
“…From electron microscopy studies, the cytoplasmic sleeve of a PD in mesophyll cells appears to be subdivided into microchannels 1.5 to 2.5 nm in diameter (Ding et al, 1992). Microinjection experiments reveal that the basal SEL of mesophyll PD is 1 kD; this SEL corresponds to a 0.75-nm Stokes radius (Tucker, 1982;Goodwin, 1983;Wolf et al, 1989) and predicts a basal diameter for a microchannel of 1.5 nm, consistent with the dimensions observed by using electron microscopy. Microinjection studies also show that PD in different cell types can have different basal SELs.…”
Section: Symplastic Transport Via Dynamic Plasmodesmal Channelssupporting
confidence: 59%
“…IP3 acts as a messenger to stimulate the relesse of calcium from intracellular stores (see Trewavas and Malhó, 1997, in this issue). In plants, IP, itself apparently moves through PD, and IP, and elevated free calcium levels decrease plasmodesmal SEL (Erwee and Goodwin, 1983;Tucker, 1988Tucker, , 1990Tucker and Boss, 1996). Potentially, the interplay between actin cytoskeletal rearrangement and physiological signals such as calcium and those in the inosito1 signaling pathway may direct the fine control of plasmodesmal permeability (Tucker and Boss, 1996).…”
Section: A Potential Role For Cytoskeletal Elements In Plasmodesmal Smentioning
confidence: 99%
“…Effective channel size is typically monitored by cellto-cell movement of differently sized, fluorescently labeled dextrans that serve as inert tracer molecules and define the size exclusion limit (SEL) of plasmodesmata. In many types of plant cells, plasmodesmal microchannels are thought to limit molecular traffic to small molecules and metabolites with a molecular mass up to 1 kD (Tucker, 1982;Goodwin, 1983;Terry and Robards, 1987;Wolf et al, 1989;Derrick et al, 1990). In a wild-type plant, only plasmodesmata of the companion cell-sieve element system of the phloem have been shown to display a higher basal SEL and mediate transport of dextrans at least 3 kD in size (Kempers et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The SEL in land plants is 1-3 kDa (Erwee and Goodwin 1983, Goodwin 1983, Terry and Robards 1987, Kempers et al 1993, Radford and White 2001. Genetic analysis of plasmodesmata showed that a high occurrence of branched plasmodesmata is related to the ability for transportation of larger molecules compared with the wild type (Kim et al 2002, Burch-Smith and Zambryski 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The size exclusion limit (SEL), which has been measured by microinjection of fluorescent tracers with different sizes is 1-3 kDa, depends on the species and cell types (Erwee and Goodwin 1983, Goodwin 1983, Terry and Robards 1987, Kempers et al 1993, Radford and White 2001. Molecular movement and SEL in plasmodesmata are regulated by a divalent ion such as Ca 2+ (Erwee and Goodwin 1983) and by degeneration/ synthesis of callose deposited at the constricted neck region of the plasmodesmata (Radford and White 2001, Zavaliev et al 2011.…”
Section: Introductionmentioning
confidence: 99%